HUBUNGAN PERSEPSI DENGAN PERILAKU REMAJA DALAM PENCEGAHAN COVID-19 VARIAN BARU OMICRON PADA SISWA SMA DI KABUPATEN TABANAN TAHUN 2022 - Dwi Mahaeswari, Anak Agung Sagung Ningrat; Kardiwinata, Made Pasek (ARCHIVE OF COMMUNITY HEALTH, 2024)
The existence of new variant COVID-19, Omicron had an effect to high increasing cases. Based on earlier study in Tabanan Regency, many people who violated health protocols. Violated was frequently found in hangout places for youngsters and most adolescents had the perception on low risk of infecting Omicron. The purpose of the research was to know relationship between adolescent perception and behavior in prevention new variant COVID-19, Omicron among high school students in Tabanan Regency. The research design is a cross sectional, 160 sample were selected using two stage cluster sampling. Data was collected using google forms and analyzed using logistic regression. The study results showed that most adolescents were classified as good in carrying out COVID-19 prevention behavior, Omicron was 79,38%. The binary logistic regression test showed that perceived susceptibility (aOR= 2,99; 95% CI: 1,05-8,53), perceived benefits (aOR= 10,69; 95% CI: 1,80-63,63), and perceived barriers(aOR= 3,94; 95% CI: 1,08-14,38) had relationship with prevention behavior. While perceived severity has no relationship with prevention behavior. Future researchers who are interested in bringing up this topic can examine more deeply the perceived susceptibility of negative adolescents' to the transmission of the new variant COVID-19, Omicron. Keywords: Perception, Prevention Behavior, Adolescents, Omicron